The Effect of Entrepreneurship Education and Entrepreneurial Motivation on ARO Gapopin’s Student Interest in Entrepreneurship - Nensi Mesrani Tarigan; Ferry Doringin; M Wahyu Budiana (Bina Nusantara University, 2022)
Indonesia has a problem related to entrepreneurship motivation and interest that must be triggered since younger age. The research aimed to determine the effect of entrepreneurship education and entrepreneurial motivation on the entrepreneurial interest of ARO Gapopin students. The population consisted of students of ARO Gapopin. The research applied a quantitative approach through a questionnaire as an instrument for 195 respondents. Data were analyzed using SPSS 16. The findings indicate the importance of entrepreneurship education and entrepreneurial motivation to increase interest in entrepreneurship for ARO Gapopin students. Interest in entrepreneurship needs to be increased by a good preparation process as a way to form and develop aspiring entrepreneurs. Some ways to form aspiring entrepreneurs include identifying entrepreneurial attitudes and behaviors, forming entrepreneurial characteristics, identifying possible factors of success and failure in entrepreneurship, and overcoming myths about entrepreneurship.